The clinical application of cortical auditory evoked potential (CAEP) in children at Malaysia tertiary hospital - Isnan, Nurnazeha (2024)
This study aim to determine the usefulness of CAEP measurement as an objective tool to assess hearing aid benefits in children. This study was divided into three consecutive phases. Phase I was about determining the test-retest reliability in adults and studying the feasibility of CAEP when testing children. On the other hand, phase II focused on comparing CAEP results elicited by different electrode montages and by different listening conditions. The correlations between CAEP outcomes, parental questionnaires (MAIS and MUSS), and aided responses in hearing-impaired children were also assessed. Subsequently, in phase III, CAEP results were compared between normal children and hearing-impaired children. This study recruited 14 hearing-impaired children and 22 normal children aged 4 to 12 years. The CAEP was recorded at two points of electrode montages (CZ and T3) for both groups using four speech stimuli, i.e., /ba/, /m/, /g/, and /t/. It was found that CAEP results elicited by all stimuli had good test-retest reliability (phase I). The CAEP testing conveniently recorded in normal and hearing-impaired children. In phase II, CAEP results were found to be comparable across the listening conditions (left, right and binaural) (p > 0.05). While no correlations were found between CAEP and aided responses (p > 0.05), some CAEP parameters showed significant correlations with MAIS and MUSS questionnaires (p < 0.05). In phase III, no significant differences in CAEP amplitudes were found between the two groups for both electrode montages (p > 0.05). For latency comparisons, except for P1 latency (CZ and T3) and N1 latency (T3), the majority of the CAEP latency results were found to be comparable between the two groups. In conclusion, the CAEP testing is indeed a useful assessment to determine the cortical function of hearing-impaired children objectively.